Sabot Front Borerider Stiffness vs. Dispersion: Finding the Knee in the Curve - Alan F. Hathaway; John R. Burnett Jr. (Shock and Vibration)
In the design of armor piercing, fin-stabilized, discarding sabot projectiles, the radial stiffness of the sabot front borerider has a significant impact on the projectile's dispersion and is, therefore, an important design consideration. Whether designing a new projectile or trying to improve an existing design, projectile designers can achieve front borerider stiffness without understanding its affect on dispersion characteristics. There is a knee in the stiffness vs. dispersion curve at which a change in the sabot front borerider stiffness will have a significant impact on dispersion or no impact at all depending on whether the stiffness is increased or decreased. The subject of this paper is an analytical approach to quantitatively determine the knee in the curve. Results from using this approach on the M865 APFSDS projectile are also presented.